The relationships between physical learning environment, psychological characteristics, and HOTS / Mohd Azry Abdul Malik … [et al.] - Abdul Malik, Mohd Azry; Adnan, Mazlini; Md Noor, Mohd Rahimie; Mustapha, Muhammad Firdaus (Research Management Centre (RMC), 2020)
The study investigates the relationships between the physical learning environment (PLE), psychological characteristics (students’ academic self-efficacy and satisfaction), and higher-order thinking skills (HOTS) in statistics education. The study also aimed to determine if psychological characteristics mediate the relationships between the PLE and HOTS. A total of 285 students were selected as samples using cluster sampling. The study instruments were adapted from Smart classroom inventory, science laboratory environment inventory, test of science-related attitudes, self-efficacy in learning and performance for college, and dimension of learning rubrics. The gathered data were analysed using Partial Least Square Structural Equation Modeling (PLS-SEM). The findings revealed that a significant direct relationship existed between PLE and HOTS. Moreover, the PLE also did influence the students’ HOTS indirectly through psychological characteristics (academic self-efficacy and satisfaction). The findings from this study give an important and valuable contribution to knowledge in the area of HOTS research in the context of Malaysian Institution of Higher Learning. The implication of this study suggests that the good quality of PLE in statistics education would influence students’ HOTS directly and also indirectly through the positive development of psychological characteristics in teaching and learning (T&L) process.